VALIDATION OF THE MALAY VERSION OF THE CANCER THERAPY SATISFACTION QUESTIONNAIRE AMONG MALAYSIAN CANCER PATIENTS - Abd Hamid, Norhaliza; Hamdan, Nur Amirah; Azman, Nizuwan; Leong Bin Abdullah, Mohammad Farris Iman (Malaysian Journal of Public Health Medicine, 2021)
Satisfaction with treatment among cancer patients is vital for planning of healthcare strategies and to ensure compliance to cancer therapy. Hence, this study translated the original English version of the Cancer Therapy Satisfaction Questionnaire (CTSQ) into Malay and investigated the reliability and validity of the Malay version for use to assess satisfaction with treatment among Malaysian cancer patients. Initially, concurrent translation and back translation of the English version of the CTSQ was performed. Then, the Malay version of the CTSQ (CTSQ-M) was administered to 200 cancer patients with different sites and stages of cancer for assessment of its reliability and validity. The CTSQ-M and its domains exhibited acceptable internal consistency (Cronbach’s ? ranged from 0.724 to 0.882). Convergent and discriminant validity were achieved by the CTSQ-M. Construct validity was achieved by the CTSQ-M as exploratory factor analysis extracted 3 factors, while confirmatory factor analysis confirmed that the CTSQ-M consisted of 16 items in 3 domains. We concluded that the CTSQ-M had acceptable psychometric properties.